Analisis Struktur Gedung Gereja Toraja Jemaat Ledo Buntao Menggunakan Sistem Rangka Pemikul Moment Biasa (Srpmb) ( Studi Kasus Gedung Gereja Toraja Jemaat Ledo Buntao Kabupaten Toraja Utara ) - Yulius Pakiding; Jeni Padang; Wilson Tandi Parubak (Journal on Education, 2023)
The research aims to analyze the redevelopment of a 2-story church building with SRPMB located near the Ledo Buntao market. The parts that will be analyzed include the upper structure (columns, beams and floor plates) while the lower structure (foundation). The loads acting on the structure refer to SNI 1727:2013 and PPIUG 1983, while for earthquake loading refer to SNI 1726:2012. For detailed requirements for reinforced concrete building structures, refer to SNI 2847:2013. The structure of the Ledo Buntao Congregation Toraja Church building which will be explained is the structure of columns, beams and floor plates. Calculation analysis was carried out manually to determine the dimensions of the structure of columns, beams and floor plates in the building, using reinforced concrete SRPMB, to determine safe dimensions by carrying out moment calculations, and analysis of the footings. The results of the analysis on the construction of the Ledo Buntao Congregational Church building obtained column dimensions. 40 x 40 cm, main beam 30 x 60 and subsidiary beams 20 x 30 cm, and for the floor plate the thickness of 12 cm is used and for the lower structure a palm foundation is used.